Hijacking Factor H for Complement Immune Evasion - Moore, Sara R.; Menon, Smrithi S.; Cortes, Claudio; Ferreira, Viviana P. (Frontiers in Immunology, 2021)
The complement system is an essential player in innate and adaptive immunity. It consists of three pathways (alternative, classical, and lectin) that initiate either spontaneously (alternative) or in response to danger (all pathways). Complement leads to numerous outcomes detrimental to invaders, including direct killing by formation of the pore-forming membrane attack complex, recruitment of immune cells to sites of invasion, facilitation of phagocytosis, and enhancement of cellular immune responses. Pathogens must overcome the complement system to survive in the host. A common strategy used by pathogens to evade complement is hijacking host complement regulators. Complement regulators prevent attack of host cells and include a collection of membrane-bound and fluid phase proteins. Factor H, a fluid phase complement regulatory protein, controls the alternative pathway (AP) both in the fluid phase of blood and on cell surfaces. In order to prevent complement activation and amplification on host cells and tissues, Factor H recognizes host cell-specific polyanionic markers in combination with complement C3 fragments. Factor H suppresses AP complement-mediated attack by accelerating decay of convertases and by helping to inactivate C3 fragments on host cells. Pathogens, most of which do not have polyanionic markers, are not recognized by Factor H. Numerous pathogens, including certain bacteria, viruses, protozoa, worms, and fungi, can recruit Factor H to protect themselves against host-mediated complement attack, using either specific receptors and/or molecular mimicry to appear more like a host cell. This review will explore pathogen complement evasion mechanisms involving Factor H recruitment with an emphasis on: (a) characterizing the structural properties and expression patterns of pathogen Factor H binding proteins, as well as other strategies used by pathogens to capture Factor H; (b) classifying domains of Factor H important in pathogen interaction; and (c) discussing existing and potential treatment strategies that target Factor H interactions with pathogens. Overall, many pathogens use Factor H to avoid complement attack and appreciating the commonalities across these diverse microorganisms deepens the understanding of complement in microbiology.